The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/jacs.5b10221
|View full text |Cite
|
Sign up to set email alerts
|

Dearomative Indole (3 + 2) Reactions with Azaoxyallyl Cations – New Method for the Synthesis of Pyrroloindolines

Abstract: Herein, we report the first examples of the synthesis of pyrroloindolines by means of (3 + 2) dearomative annulation reactions between 3-substituted indoles and highly reactive azaoxyallyl cations. Computational studies using density functional theory (DFT) (B3LYP-D3/6-311G**++) support a stepwise reaction pathway in which initial C–C bond formation takes place at C3 of indole, followed by ring closure to give the observed products. Insights gleaned from these calculations indicate that the solvent, either TFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 172 publications
(68 citation statements)
references
References 38 publications
4
64
0
Order By: Relevance
“…Conversion of 10 into the vinyl compound 11 required three steps:1 )deacetylation (95 %), 2) conversion into the bis-(alkyliodide) (92 %), and 3) finally double E 2 elimination (85 %) to give 11 in 74 %yield for the three steps combined. Finally,adouble cross-metathesis with the terminal alkene 12 (excess) using ac atalytic amount of the Hoveyda-Grubbs II catalyst allowed the formation of the symmetrical target nigramide R ( 13). Thes pectroscopic data for this compound was avery good match with that reported in the literature.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Conversion of 10 into the vinyl compound 11 required three steps:1 )deacetylation (95 %), 2) conversion into the bis-(alkyliodide) (92 %), and 3) finally double E 2 elimination (85 %) to give 11 in 74 %yield for the three steps combined. Finally,adouble cross-metathesis with the terminal alkene 12 (excess) using ac atalytic amount of the Hoveyda-Grubbs II catalyst allowed the formation of the symmetrical target nigramide R ( 13). Thes pectroscopic data for this compound was avery good match with that reported in the literature.…”
supporting
confidence: 67%
“…Initially,w e found that aw ide range of standard solvents were not compatible with the reaction at all and only starting material was recovered. We noted that hypervalent iodine reagents are sometimes used in fluorinated solvents [3,13] and therefore we screened hexafluoroisopropanol (HFIPA) for the dimerization. Pleasingly,t he reaction began to work well, and the addition of 10 mol %IBX formed 2a in 39 %yield (entry 1).…”
mentioning
confidence: 99%
“…[23][24][25] Our group has a longstanding interest in the reaction of indoles and related heterocycles. [26][27][28][29] Herein, we disclose a new approach for the intermolecular C3 arylation of unprotected indoles with simple aryl halides. The reaction is promoted by KOtBu and does not require the use of transition metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[2629] Herein, we disclose a new approach for the intermolecular C3 arylation of unprotected indoles with simple aryl halides. The reaction is promoted by KO t Bu and does not require the use of transition metal catalysts.…”
mentioning
confidence: 99%